Natriuretic peptide receptors regulate cytoprotective effects in a human ex vivo 3D/bioreactor model - Peake, Nicholas (BioMed Central, 2013)
INTRODUCTION: The present study examined the effect of C-type natriuretic peptide (CNP) and biomechanical signals on anabolic and catabolic activities in chondrocyte/agarose constructs. METHODS: Natriuretic peptide (Npr) 2 and 3 expression were compared in non-diseased (grade 0/1) and diseased (grade IV) human cartilage by immunofluoresence microscopy and western blotting. In separate experiments, constructs were cultured under free-swelling conditions or subjected to dynamic compression with CNP, interleukin-1β (IL-1β), the Npr2 antagonist P19 or the Npr3 agonist cANF(4-23). Nitric oxide (NO) production, prostaglandin E(2 )(PGE(2)) release, glycosaminoglycan (GAG) synthesis and CNP concentration were quantified using biochemical assays. Gene expression of Npr2, Npr3, CNP, aggrecan and collagen type II were assessed by real-time qPCR. Two-way ANOVA and a post hoc Bonferroni-corrected t-test were used to analyse the data. RESULTS: The present study demonstrates increased expression of natriuretic peptide receptors in diseased or older cartilage (age 70) when compared to non-diseased tissue (age 60) which showed minimal expression. There was strong parallelism in the actions of CNP on cGMP induction resulting in enhanced GAG synthesis and reduction of NO and PGE(2 )release induced by IL-1β. Inhibition of Npr2 with P19 maintained catabolic activities whilst specific agonism of Npr3 with cANF(4-23 )had the opposite effect and reduced NO and PGE(2 )release. Co-stimulation with CNP and dynamic compression enhanced anabolic activities and inhibited catabolic effects induced by IL-1β. The presence of CNP and the Npr2 antagonist abolished the anabolic response to mechanical loading and prevented loading-induced inhibition of NO and PGE(2 )release. In contrast, the presence of the Npr3 agonist had the opposite effect and increased GAG synthesis and cGMP levels in response to mechanical loading and reduced NO and PGE(2 )release comparable to control samples. In addition, CNP concentration and natriuretic peptide receptor expression were increased with dynamic compression. CONCLUSIONS: Mechanical loading mediates endogenous CNP release leading to increased natriuretic peptide signalling. The loading-induced CNP/Npr2/cGMP signalling route mediates anabolic events and prevents catabolic activities induced by IL-1β. The CNP pathway therefore represents a potentially chondroprotective intervention for patients with OA, particularly when combined with physiotherapeutic approaches to stimulate biomechanical signals.